High Precision U/Th Dating of First Polynesian Settlement - Burley, David; Weisler, Marshall I.; Zhao, Jian-xin (PLOS ONE, 2012)
Previous studies document Nukuleka in the Kingdom of Tonga as a founder colony for first settlement of Polynesia by Lapita peoples. A limited number of radiocarbon dates are one line of evidence supporting this claim, but they cannot precisely establish when this event occurred, nor can they afford a detailed chronology for sequent occupation. High precision U/Th dates of Acropora coral files (abraders) from Nukuleka give unprecedented resolution, identifying the founder event by 2838±8 BP and documenting site development over the ensuing 250 years. The potential for dating error due to post depositional diagenetic alteration of ancient corals at Nukuleka also is addressed through sample preparation protocols and paired dates on spatially separated samples for individual specimens. Acropora coral files are widely distributed in Lapita sites across Oceania. U/Th dating of these artifacts provides unparalleled opportunities for greater precision and insight into the speed and timing of this final chapter in human settlement of the globe.